2018
DOI: 10.3390/su10114322
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Barriers to Clean Cooking: A Systematic Literature Review from a Consumer Behavior Perspective

Abstract: A lack of access to clean energy and use of traditional cooking systems have severe negative effects on health, especially among women and children, and on the environment. Despite increasing attention toward this topic, few studies have explored the factors influencing consumers’ adoption of improved cooking stoves (ICS). This systematic literature review (n = 81) aims to identify the main drivers and barriers to clean cooking from a consumer perspective. In addition, it aims to define how consumers perceive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 107 publications
(431 reference statements)
2
71
0
1
Order By: Relevance
“…higher household asset index, education level, household size-figure 3(a)) with switching to cleaner fuels. This observation was consistent with findings from systematic reviews of enablers to clean fuel adoption [52,53,73]. Among all household SES variables included in this analysis, increasing household size (number of rooms) was the strongest independent predictor of polluting-to-clean fuel switching in all countries.…”
Section: Household Factorssupporting
confidence: 88%
“…higher household asset index, education level, household size-figure 3(a)) with switching to cleaner fuels. This observation was consistent with findings from systematic reviews of enablers to clean fuel adoption [52,53,73]. Among all household SES variables included in this analysis, increasing household size (number of rooms) was the strongest independent predictor of polluting-to-clean fuel switching in all countries.…”
Section: Household Factorssupporting
confidence: 88%
“…Accordingly, 38.2% of bitumen goes to final consumption and is used mainly in the industrial sector (98.3%) -metallurgical industry -and in housing and commercial sector (1.7%) -for residential heating. (Vigolo et al, 2018;Wellinger et al, 2013;Zakeri and Syri, 2015;Meynkhard, 2020b;Meynkhard, 2019b;Trubnikov et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Other factors that can influence the uptake of the gasifier include household head education, household income, household size, fuelwood prices and access to credit [51,52] and not being able to perform certain tasks effectively such as warming space and easy roasting of foods [20]. Other factors highlighted to affect the adoption of improved cook stoves (ICSs) in the systematic review on drivers and barriers to clean cooking by Vigolo et al [22] include low income, perception that ICSs are expensive, resistance toward new technology, rural locations and low awareness of the negative impacts of traditional cook stoves by the users. In this study, in order to investigate the user aspects without cost limitations, the households were given the gasifiers for free.…”
Section: Challenges With the Use Of The Gasifier Stovementioning
confidence: 99%
“…Research on the use of gasifier cookstoves for biochar production has shown the potential to reduce emissions and fuel consumption [20,21], but there is a need for knowledge on the implications of their uptake from the users' perspective, which this study contributes to. Further, a systematic review by Vigolo et al [22] reported low awareness on the environmental and health impacts of improved cook stoves by stove users. The aim of this study was therefore to assess the benefits of top-lit-updraft (TLUD) (natural draft) gasifier cook stoves (hereafter "gasifier") uptake from a holistic perspective, based on data obtained from a survey of the 50 households in Kwale County in Kenya who were issued with gasifiers for free.…”
Section: Introductionmentioning
confidence: 99%